1996
DOI: 10.1002/(sici)1096-9861(19960212)365:3<491::aid-cne11>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-immunoreactive neurons in the adult rabbit retina

Abstract: Somatostatin (SRIF) is a neuroactive peptide that is distributed throughout the nervous system, including the retina. This peptide has been localized to populations of amacrine cells in a variety of vertebrate species. In the rabbit retina, SRIF immunoreactivity is present in a sparse population of medium to large neurons (13.72 microns in diameter, or 147.84 mu 2) in the ganglion cell layer and in a small number of neurons in the inner nuclear layer. These cells display a preferential distribution to the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
1
21
1
Order By: Relevance
“…Immunostained fibers were also occasionally seen entering either the GCL or the INL. However, we did not see labeled fibers extending into the OPL, which is in contrast to the report by Rickman et al (1996). With the exception of the thick proximal dendrites, most of the SOM‐immunopositive processes in the IPL had small diameters of approximately 0.5 μm and possessed numerous varicosities.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Immunostained fibers were also occasionally seen entering either the GCL or the INL. However, we did not see labeled fibers extending into the OPL, which is in contrast to the report by Rickman et al (1996). With the exception of the thick proximal dendrites, most of the SOM‐immunopositive processes in the IPL had small diameters of approximately 0.5 μm and possessed numerous varicosities.…”
Section: Resultscontrasting
confidence: 99%
“…The neurochemically identified amacrine cell types studied here have been shown to match the morphological profiles of those falling within the polyaxonal amacrine cell class types (Versaux‐Botteri et al, 1984; Sandell, 1985; Sagar, 1986, 1987; White et al, 1990; Dacey, 1990; Tauchi et al, 1990; Cuenca et al, 1995; Perez et al, 1995; Rickman et al, 1996; Cuenca and Kolb, 1998; Oh et al, 1999). In rabbit retina, two extensive studies of the polyaxonal amacrine cells showed that they include up to six different morphological subtypes, with different response and receptive field properties (Famiglietti, 1992a, b, c; Völgyi et al, 2001).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations